Essential writings - Gutiérrez, Gustavo (Maryknoll, N.Y Orbis Books, 1996)
Part of The Making of Modern Theology series, this thorough introduction includes, in one volume, the whole range of Gutierrez's thought--biblical, theological, methodological, and historical. This work also features a select bibliography of works by and on Gutierrez.
Includes bibliographical references (p. 334) and index.
Keywords: Liberation theology